Increasing Knowledge and Skills of Pokdarwis through Making Interior Products and Souvenirs Based on Local Wisdom - Prihatiningrum, Atik; Panji Anom Ramawangsa; Diyas Widiyarti (International Journal of Community Service Learning, 2024)
Community-based tourism development is an important strategy in improving the welfare of local communities, especially in tourist villages. The Tourism Awareness Group (Pokdarwis) has a strategic role in managing tourism potential in a sustainable manner, but often faces challenges in the aspects of knowledge and skills to create added value through creative products. Making interior products and souvenirs using bamboo aims to increase the knowledge and skills of Pokdarwis in processing bamboo into environmentally friendly products based on local wisdom. The aim of this research is to improve the skills of Pokdarwis in designing product designs, composing shapes using tools effectively, and introducing the products that have been produced to the general public as strengthening the role of Pokdarwis in realizing Sapta Pesona. Implementation of activities uses a participatory learning and action approach with stages of socialization, application of technology, training and assistance in making products. Data obtained from pre-test and post-test results and processed using qualitative descriptive analysis. The results of this activity were an increase in knowledge by an average of 90% for the 10 participants and an increase in the skills of the Pokdarwis in processing bamboo into interior products and souvenirs which produced glasses, cups and room partitions with lumbon and rafflesia motifs which represent unique local values. The implications of this research are Increasing the knowledge and skills of Pokdarwis members will strengthen their role in managing village tourism, especially in creating creative products based on local wisdom.